Services écosystémiques et adaptation urbaine interscalaire au changement climatique : un essai d’articulation - Aleksandar Rankovic; Chantal Pacteau; Luc Abbadie (VertigO)
Interest in the links between vegetation and urban climate dates rather far back in the history of ideas, but it takes a whole new dimension when reframed as an "ecosystem services and climate change adaptation" problem. This new association calls for articulation and evaluation, and thus implies a review of the different issues encountered when exploring the link between ecosystems and urban adaptation to climate change. In this paper, we first give an overview of the concept of "ecosystem services". We suggest a framework to analyse the usefulness of this notion in the design of urban adaptation strategies. We then review ecosystem services and disservices in relation with urban adaptation, arguing that this requires an integrated approach. Last, we tackle cross-scale interactions that are inherent to urban sustainability design, and question the greenway concept regarding its relevance to cross-scale urban adaptation to climate change.